Teacher-centered or Student-centered Learning Approach to Promote Learning? - Ive Emaliana (Institut Teknologi Sepuluh Nopember, 2017)
This study investigates English department students learning needs includingtheir attitudes towards student-centered and traditional teaching approaches,culture learning in English as Foreign Language (EFL) program, attitudestowards authority in class, the main problems encountered in the course inlearning English and their practice of language learning strategies. In thisempirical study, following Xiao’s (2006) questionnaire, the data are collectedfrom undergraduates and postgraduates students. In analyzing the groups,one-way ANOVA Test is used to identify whether the mean score on a variablediffered significantly from one group to another by taking into accountvariation within groups as well as between groups. The findings of thisresearch provide EFL teachers with insightful information on students’learning needs as an input to syllabus and material planning, to lessonplanning and classroom instruction practice. The study demonstrates theimportance of a good understanding of students’ variables in TEFL programsat university level in Indonesia.